Estimativas da área da folha de figueiras 'Roxo de Valinhos' usando dimensões lineares do limbo foliar - Souza, Adilson Pacheco De; Silva, Andréa Carvalho Da; Leonel, Sarita [UNESP]; Souza, Manoel Euzébio De; Tanaka, Adriana Aki (Universidade Federal de Santa Maria, 2014)
This study aimed to generate and validate models to estimate the area of leaf of ​​fig tree 'Roxo de Valinhos' using linear measurements easily taken. It was collected 600 leaves, including the maximum variation in size, age and shape of leaves, wherefore, 200 leaves were used in the validation of the regressions. The statistical indicators MBE, RMSE, adjustment index and performance index were applied to evaluate the performance of 51 models estimate, derived from the application of measures of length, width and transversal, and their interactions together. The best results were obtained using the equations AF=0,1289(C+C1+C2)1,8450 and AF=0,9781[(C+C1+C2)/3]1,8451, which provide deflections and scatterings of 0.63 and 47.85cm², with adjustments, correlations and performance of 91, 95 and 87%, respectively. In the estimates based on only one measure it should be applied the equation AF=2,879C1,5451

Neste estudo, objetivou-se gerar e validar modelos de estimativa da área da folha da figueira 'Roxo de Valinhos' a partir de medidas lineares de fácil obtenção. Foram coletadas 600 folhas, incluindo-se o máximo de variabilidade quanto ao tamanho, idade e formato, sendo, destas, 200 empregadas na validação das regressões. Empregaram-se os indicativos estatísticos MBE, RMSE, índice de ajustamento e índice de desempenho para avaliação da performance de 51 modelos estimativa, obtidos com base nas aplicações das medidas de comprimento, largura e transversal da folha e suas respectivas interações. Os melhores resultados foram obtidos pelas equações AF=0,1289(C+C1+C2)1,8450 e AF=0,9781[(C+C1+C2)/3]1,8451, que propiciam desvios e espalhamentos de 0,63 e 47,85cm², com ajustamentos, correlações e desempenhos superiores a 91, 95 e 87%, respectivamente. Nas estimativas com base em apenas uma medida, deve-se aplicar a equação AF=2,879 C1,5451.
Estimates of leaf area of fig tree 'Roxo de Valinhos' using linear dimensions of the leaf blade
Keywords: Ficus carica L.; medidas foliares; análise de crescimento; Ficus carica L.; leaf measures; growth analysis